2013
DOI: 10.1007/s00234-013-1180-7
|View full text |Cite|
|
Sign up to set email alerts
|

Susceptibility weighted imaging depicts retinal hemorrhages in abusive head trauma

Abstract: IntroductionThis study aims to evaluate the capability of magnetic resonance imaging (MRI) susceptibility weighted images (SWI) in depicting retinal hemorrhages (RH) in abusive head trauma (AHT) compared to the gold standard dilated fundus exam (DFE).MethodsThis is a retrospective, single institution, observational study on 28 patients with suspected AHT, who had a DFE and also underwent brain MRI-SWI as part of routine diagnostic protocol. Main outcome measures involved evaluation of patients to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…A key application of SWI is aiding the diagnosis of diseases involving cerebral vascular pathology. These changes include, for example, vascular malformations (e.g., arteriovenous malformations and cerebral cavernous malformations), restrictions in blood flow (e.g., developmental venous anomaly) and hemorrhages (caused by e.g., cerebral amyloid angiopathy, stroke, and traumatic injuries) (1,3,(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89). In these cases, a common source of contrast is oxygenation-related susceptibility changes occurring in blood products (3).…”
Section: Swi Of Cerebral Vascular Pathologymentioning
confidence: 99%
“…A key application of SWI is aiding the diagnosis of diseases involving cerebral vascular pathology. These changes include, for example, vascular malformations (e.g., arteriovenous malformations and cerebral cavernous malformations), restrictions in blood flow (e.g., developmental venous anomaly) and hemorrhages (caused by e.g., cerebral amyloid angiopathy, stroke, and traumatic injuries) (1,3,(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89). In these cases, a common source of contrast is oxygenation-related susceptibility changes occurring in blood products (3).…”
Section: Swi Of Cerebral Vascular Pathologymentioning
confidence: 99%
“…The investigators reported high interobserver and intraobserver reliability among pediatric ophthalmologists. Zuccoli et al [37] compared susceptibility weighted MRI to the dilated fundoscopic exam, the gold standard, at identifying retinal hemorrhages. The authors reported an MRI sensitivity of 83%, supporting its potential as a diagnostic tool and its utility when a dilated fundoscopic exam is not possible.…”
Section: Mechanism For Retinal Injury and Standardizing Retinal Findingsmentioning
confidence: 99%
“…Routine MRI brain protocols that include GRE sequences can depict retinal hemorrhages, with increased sensitivity for higher-grade hemorrhages (Figs 20, 21) (54). High-resolution susceptibility-weighted imaging of the orbit can further increase MRI sensitivity for detecting retinal hemorrhage and can be useful when the finding cannot be seen clinically (55).…”
Section: Retinal Hemorrhagementioning
confidence: 99%